2014
DOI: 10.1128/jb.00938-13
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Flagellar Genes in Exponential Phase by CsgD and CpxR, Two Crucial Modulators of Escherichia coli Biofilm Formation

Abstract: e Escherichia coli adapts its lifestyle to the variations of environmental growth conditions, swapping between swimming motility or biofilm formation. The stationary-phase sigma factor RpoS is an important regulator of this switch, since it stimulates adhesion and represses flagellar biosynthesis. By measuring the dynamics of gene expression, we show that RpoS inhibits the transcription of the flagellar sigma factor, FliA, in exponential growth phase. RpoS also partially controls the expression of CsgD and Cpx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 64 publications
(99 reference statements)
4
40
1
Order By: Relevance
“…Pronounced motility was observed for Tob1, reduced motility for Fec67, Fec101, No.12, and B‐8638, whereas strains B‐11870 and 80//6 were nonmotile (Figure e). Swimming motility was csgD ‐independent, since csgD deletion mutants of strains Tob1 and No.12 displayed similar swimming behavior as the respective wild types (Figure S1), in contrast to a previous study (Dudin, Geiselmann, Ogasawara, Ishihama, & Lacour, ).…”
Section: Resultscontrasting
confidence: 82%
“…Pronounced motility was observed for Tob1, reduced motility for Fec67, Fec101, No.12, and B‐8638, whereas strains B‐11870 and 80//6 were nonmotile (Figure e). Swimming motility was csgD ‐independent, since csgD deletion mutants of strains Tob1 and No.12 displayed similar swimming behavior as the respective wild types (Figure S1), in contrast to a previous study (Dudin, Geiselmann, Ogasawara, Ishihama, & Lacour, ).…”
Section: Resultscontrasting
confidence: 82%
“…CsgD is a transcription factor that positively regulates the csgBAC operon (Zogaj et al, 2003; Dudin et al, 2014). The csgBAC operon encodes the major and minor curli fiber components, CsgA and CsgB, respectively (Hammar et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Dudin et al (19) recently found that CsgD can directly inhibit the transcription of fliA, which encodes the sigma factor ( F ) that directs the expression of the late (class 3) flagellar genes. This might provide a more direct regulatory link between CsgD and motility.…”
Section: Resultsmentioning
confidence: 99%
“…Other sources of the motility defect in the ⌬hns strain involve the biofilm regulator CsgD, which is strongly upregulated in the ⌬hns mutant and which was recently shown to inhibit transcription of the fliA (19) as well as of the fliE and fliF (32) operons. Each of these repressing actions appears significant under some conditions.…”
Section: Discussionmentioning
confidence: 99%